The "holy girl": Laura Vicuña in hagiographies and historical biographies (1911-1990) (Tempo e Argumento, 2023)
Holiness is a historical construct whose approach allows us to range from hagiographic and biographical texts, which nourish the canonization process in the Catholic Church, to the social environment of a saint, in this case of Blessed Laura del Carmen Vicuña (1891-1904). This girl was a student of the Daughters of Mary Help of Christians, a congregation of religious women founded by Don Bosco and Mother Mazzarello in Italy, in 1872. To do this, we have selected and classified a set of hagiographies and biographies as historical sources, in order to analyze them using the hermeneutics of this subject. The aim is to observe how a society grants one of its members traits of holiness to take it to the altars. The first biographical set corresponds to the first hagiographies written between 1911 and 1945 by the Salesian Augusto Crestanello and the Daughters of Mary Help of Christians M. Puttini (Maria Magdalena Moretti) and Alba Nembri. These hagiographies build Laura's holiness based on her submission to the Cause of Saints in the Vatican for beatification. The biographies of the second period, between 1958 and 1990, contain debates that seek to verify historical facts and find the "true" face of Laura. The Salesians Raúl Entraigas, Luigi Càstano, and Ciro Brugna emphasize the historical context and that of the Salesian missions. Without leaving the hagiographic section, the authors search for historical documentation on some issues related to the making of her sanctity, such as the legitimacy of Laura's birth and her face.
Keywords: holiness; Laura Vicuña; Paragonia; Daughters oj Mary Help of Christians